Torbjörn Bergman and Erik Damgaard (eds.), Delegation and Accountability in European Integration. The Nordic Parliamentary Democracies and the European Union, London and Portland: OR: Frank Cass, 2000, 180 s., £17,50. - Kelstrup, Morten (Politica, 2001)
-